PENGARUH STRATEGI SEGMENTING, TARGETING DAN POSITIONING (STP) TERHADAP VOLUME PENJUALAN PADA PT. BALIYONI SAGUNA DENPASAR - Bandi, Sekar Chornelia; Fanggidae, Rolland; Salean, Debryana Y; Fanggidae, Apriana H.J (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
The purpose of this study was to determine the effect of segmenting, targeting and positioning strategies partially and simultaneously on sales volume at PT Baliyoni Saguna Denpasar which is an e-purchasing company, where the government of the island of Bali is a regular consumer of the company. This type of research is survey research with a quantitative research approach. The population in this study were employees of PT Baliyoni Saguna. This study used a sample of 30 respondents using purposive sampling technique, namely judgment sampling. The analysis techniques used are descriptive statistical analysis, multiple linear regression analysis, coefficient of determination, classical assumption test and hypothesis testing through t test and F test. The data collection technique was carried out by interview and distributing questionnaires via google form. The results showed that simultaneously segmenting, targeting and positioning strategies had a positive and significant effect on sales volume. Meanwhile, simultaneously segmenting and targeting strategies have a positive and significant effect on sales volume while positioning strategies have a negative and significant effect on sales volume